Housing Cycles and Macroeconomic Fluctuations: A Global Perspective - Ambrogio Cesa-Bianchi (Inter-American Development Bank (IDB), 2012)
This paper investigates the international spillovers of housing demand shocks on real economic activity. The global economy is modelled using a Global VAR, with a novel house price data set for both advanced and emerging economies. The impulse responses to an identified US housing demand shock confirm the existence of strong international spillovers to advanced economies. In contrast, the response of some major emerging economies is not significantly different from zero. The paper also shows that synchronized housing demand shocks in advanced economies reinforce each other and have a deep and long-lasting impact on economic activity.
Keywords: C32; E44; F44; 330